Brain drain and brain circulation : a study of South Africans in the United Arab Emirates. - Fourie, Anco (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2006.